Design of a slurry loop for cuttings transport studies in hard rock drilling applications - Kamyab, Mohammadreza; Rasouli, Vamegh; Cavanough, G.; Mandal, S. (Canadian Institute of Mining, Metallurgy and Petroleum, 2013)
Transportation of the fluid and slurry (fluid and solid particles mixture) in the pipe and annulus space has been the focus of numerous studies. There are different parameters to be considered when studying slurry transportation. These include slurry velocity or flow rates; fluid properties such as density and rheology; and solid particles properties including concentration, density, shape and size. Also the angle of the flow conduit, rotation of the pipe and possible eccentricity of the annulus are other factors which influence slurry transport characteristics. Although a number of analytical, numerical and empirical equations as well as numerical simulations have been developed for studying the flow and slurry transport, the results need to be validated against either field or lab data. As performing field tests is costly and time consuming conducting simulations at laboratory scale appears as a good alternative. Different flow loops have been designed to study the slurry transport in different science and engineering disciplines including oil and gas and mining. However, few of these consider in particular cuttings transportation in small size annulus space. The flow characteristics appear to be very different when it travels within a small size annulus, in particular when the fluid velocity is high. In this study, a review of some of the existing slurry flow loops will be conducted. Then the details of a slurry loop which has been designed and commissioned for the purpose of studying cuttings transport in a small size annulus space for applications in drilling mineral exploration wells using coil tube technology will be presented.